A new type of two-supply, one-return, triple pipe-structured heat loss model based on a low temperature district heating system. (1st March 2021) - Xu, Qian; Wang, Kang; Zou, Zhenwei; Zhong, Liqiong; Akkurt, Nevzat; Feng, Junxiao; Xiong, Yaxuan; Han, Jingxiao; Wang, Jiulong; Du, Yanping
Abstract: Based on the design concept of a fourth-generation smart pipe network system, this paper innovatively proposes a new TOTS (Two-supply/One-return, triple pipe structure) arrangement method for district heating systems. Moreover, to accurately predict the heat loss due to the pipeline operation of the multi-pipe system, based on the multipole calculation method, a new heat loss theoretical analytical model for the TOTS was created; additionally, a corresponding three-dimensional numerical simulation model was established, which was analyzed and numerically solved. The results showed that in comparison with thermal loss data measured by Danfoss et al., the above analytical and numerical models have a high accuracy, and the deviation is within 2%. Additionally, through calculations, it was found that the distance between the heating pipes is an important factor that affects the total heat loss from the new multi-control heating system and the actual heat exchange between pipes. Highlights: A new type of TOTS arrangement method is proposed. A mathematical model of the heat loss for the multi-tube system was established. A 3D numerical simulation model for the multi-pipe system was established. The effects of the water supply pipes spacing on heat loss were studied.